KARAKTERISTIK PERUSAHAAN DI BURSA EFEK INDONESIA, REPUTASI KANTOR AKUNTAN PUBLIK DAN KETEPATWAKTUAN PELAPORAN KEUANGAN - Darmiari, Ni Putu Desy; Ulupui, I Gusti Ketut Agung (E-Jurnal Akuntansi, 2014)
Financial information must have relevance and reliability to be used as basis for decision making. Timeliness regard with aspects of relevance. This study examines the effect company characteristics that use variables of industry type, company size, profitability, complexity of operations, and company age, and audit firm reputation the timeliness of financial reporting at Indonesian Stock Exchange in 2012. Purposive sampling was done to sampling method and aquired 323 companies. The analysis using multiple linear regression. The analysis finds the industry type, company size, profitability, company age and audit firm reputation affects timeliness of financial reporting, while complexity of operation has no effect timeliness of financial reporting.
Keywords: timeliness, company characteristic, audit-firm reputation